(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
This article explores the establishment, purpose, and impact of the “Youth Leader” position in Uzbekistan, an initiative introduced to strengthen youth policy, enhance civic participation, and address socio-economic challenges among the younger generation. The study examines the origins of the role, the qualifications and duties of youth leaders, and their influence on local governance, education, and social development. It further discusses how this position contributes to the broader national strategy for empowering youth as active participants in state and community building.